Criminalizing Blasphemy in the Digital Era: A Duel of Norms between the Criminal Code and the ITE Law - Muhammad Mustadhzam; Airlangga Putera; Muhammad Zulkifli Muhdar (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine how the qualifications of the crime of blasphemy in the perspective of the criminal code and the law on information and electronic transactions. This study uses the research method used is the normative method, namely a legal research method that is sourced from regulatory and secondary document data in the form of collection from library and tertiary materials which are documents containing concepts and information such as dictionaries. The results of this study indicate that there are several qualifying elements if someone is caught in a case of blasphemy in the criminal code and the law on information and electronic transactions. In this case, the perpetrators who are included in the act of blasphemy are in Article 300 to Article 305 of the Criminal Code and Article 28 paragraph 2 of the law on information and electronic transactions which discusses the act of blasphemy. This research recommendation states that there is a need for effectiveness in the criminal code and the law on information and electronic transactions in determining punishment for someone who commits the crime of blasphemy because there are many acts of blasphemy in the community but there is not much movement from the authorities in dealing with the crime of blasphemy, therefore religious scholars and law enforcers need to take firm action in anticipating acts of blasphemy.